Online child sexual grooming discourse - Lorenzo-Dus, Nuria (Cambridge elements Elements in forensic linguistics, 2023)
"This Element examines technology-assisted grooming of children for sex - henceforth, online grooming - as an illegal practice of communicative manipulation and, as such, something that research within the academic field of forensic linguistics is ideally placed to help counter"--